Makna Hidup dan Subjective Well-Being Mahasiswa - Evany Victoriana; Rosida Tiurma Manurung; Endeh Azizah; Mia Teresa; Zuster Alvin Gultom (Humanitas (Jurnal Psikologi), 2023)
Subjective well-being, or happiness, is essential for all individuals, including university students. The purpose of this study was to examine the relationship between meaning in life and subjective well-being in college students. The respondents to this study were 261 Y university students in Bandung. The research method used in this study is a quantitative method that involved the use of questionnaires to collect data. The questionnaires used in this research were the Meaning in Life Questionnaire (MLQ), the Satisfaction with Life Scale (SWLS), and PANAS (Positive Affect and Negative Affect Schedule). Research data were analyzed using Pearson's correlation. The results of data processing show that there is a positive correlation between meaning in life and subjective well-being. This study also found that aspects of meaning in life (presence of meaning in life and searching for meaning in life) correlate with aspects of subjective well-being (life satisfaction, positive affect, and negative affect). Moreover, searching for meaning is not correlated with negative affect. Through this research, it was concluded that the more students have meaning in life, the more they will be able to achieve high subjective well-being, which is characterized by having satisfaction in life, dominated by positive affect compared to negative affect. Keywords: meaning in life, subjective well-being, university student